Diversification Strategies Among Small-Medium Enterprises: Embracing Practical Solutions in the Implementation of Indah Teraju Sdn. Bhd. - Kamarudin, Muhamad Ali Imran; Jais, Juraifa; Sidek, Syamsuriana; Jaaffar, Abdul Rahman; Mohamad, Maliani (2023)
Small Medium Enterprises (SMEs) known as the driver for both developing and developed economics including Malaysia. This category of business faced various challenges internally and externally which refrain them from growing and sustaining. From there, SME businesses initiate various initiative to overcome those challenges and one of the initiatives is through diversification strategy. However, implementing the strategy is not a guarantee success for SME entrepreneurs where various hurdles and challenges were faced. Practical intervention deemed as the key to successfully implement, subsequently lead towards favourable results for the business. Therefore, this study aims to understand the practical intervention took placed by one of the steadily-growing diversified SME in Malaysia namely, Indah Teraju Sdn. Bhd. (ITSB). The proposed model of intervention strategy in diversification implementation among SMEs is conceptualized based on the Resource-Based View and the absorptive capacity theory. It is employed an in-depth one-on-one interview with ITSB’s business owner and the data is analyzed through thematic analysis using NVivo12 software. Findings of this study revealed that ITSB implemented practical solution in terms of exploiting its’ existing networking while leveraging its’ interpersonal strengths. Also, the business adapting the current promotional strategies using social media for their marketing strategy. This study offers practical implication to the relevant stakeholders namely government agencies whom conducting entrepreneurial training and development program for SMEs as well as SME entrepreneurs themselves to focus on practical solution on diversification strategy implementation. While from the policymaker perspective, the design of training and development program should consider soft skills acquisition such as competitiveness, resilient, creativity and innovation among SMEs.